2021
DOI: 10.5115/acb.20.161
|View full text |Cite
|
Sign up to set email alerts
|

The amelioration of nicotine-induced reproductive impairment in male mouse by Sambucus ebulus L. fruit extract

Abstract: Nicotine as a toxic agent in cigarette smoke impairs the reproductive system. Sambucus ebulus extract (SEE) is shown to have some beneficial effects such as antioxidant properties. The aim of this study was to evaluate the effects of SEE on the hormones of the pituitary-gonadal axis, lipid peroxidation index, antioxidant enzymes, spermatogenesis, and epididymal sperm parameters in male mice treated with nicotine. Adult male mice were divided into five groups; A: normal saline, B: 1 mg/kg nicotine, C: 1 mg/kg n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The conversion of nicotine into OH• is responsible for the majority of its harmful effects on tissues, including lipid peroxidation (Mohammadghasemi et al 2021). DNA, proteins, and enzymes, particularly lipid peroxidation enzymes, are damaged by severe oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of nicotine into OH• is responsible for the majority of its harmful effects on tissues, including lipid peroxidation (Mohammadghasemi et al 2021). DNA, proteins, and enzymes, particularly lipid peroxidation enzymes, are damaged by severe oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…( 4)Lower testosterone levels were always associated with fewer Leydig cells and Sertoli cells of the testes affected by nicotine (17). From various studies, it was evident that the testosterone levels in all nicotine-treated rats were similar (12).…”
Section: Discussionmentioning
confidence: 98%
“…Th might reveal the intensity of the toxicity, the cellular site of the damage, and the effect of Sphaeranthus amaranthoides on Nicotine's negative effects in male albino rats. We wanted to assess the possible effects of sphaeranthus amaranthoides on nicotine-induced reproductive toxicity in this animal by quantifying changes in nicotine-induced male reproductive organs at the light microscopic level.Toxic agents such as nicotine and other substances that negatively impact the male reproductive system may be mitigated by antioxidant compoundspresent in herbal plants (12). This study was designed to analyzethe effects of Spheranthus amaranthoides against nicotine-induced male offspring of Wistar rats.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, researchers have shown that nicotine causes fertility disorders in both genders [ 3 , 4 ]. Physiology of endocrine glands of pituitary, thyroid, adrenal, testis and ovary altered following nicotine treatment [ 2 , 4 , 5 ]. Changes in sex hormones following the impact of nicotine appear to affect the release of hypothalamic-releasing hormones through hypothalamic-pituitary–gonadal (HPG) axes, such as luteinizing hormone-releasing hormone (LHRH) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…FSH levels in women smokers are higher than non-smokers [ 6 ]. Nicotine affects the morphology of the female reproductive tract in animal studies [ 5 , 7 ]. It not only disrupts the luteal phase by inhibiting progesterone secretion [ 8 ], but also causes morphological changes in the endometrium and epithelium of the fallopian tubules, and reduces the number of glands and mucosal folds [ 5 ].…”
Section: Introductionmentioning
confidence: 99%